Preparação e caracterização de hidrogel com nanopartícula de cério, Calendula officinalis ou Bixa orellana L., como potenciais curativos de feridas crônicas - Rezende, Talita Colombi (2018)
The development of new technologies and discovery of new resources has a great advance the treatment of wounds, improving the patients life quality. Thus, throughout the world there has been a growing interest in using the hydrogel for applications as wound dressings, since they favor pain relief. In addition, hydrogels can also be applied as matrices to the principle controlled release system. The aim of this work was to incorporate the cerium nanoparticle, the Calendula officinalis and the Bixa orellana L. as active in hydrogel membranes in order to evaluate the efficiency in the healing. The cerium nanoparticle, the Calendula officinalis and the Bixa orellana L. are actives which are excellent antioxidant and antibacterial anti-inflammatory properties. The study of mechanical, physical-chemical properties and “in vivo” biocompatibility of poly (vinylpyrrolidone) (PVP) hydrogel membranes obtained by gamma cross-linking was carried out. The membranes prepared in this study are characterized by swelling, gel-fraction, traction test, scanning electron microscopy, X-ray diffraction, transmission electron microscopy and atomic force microscopy. A synthesized hydrogel matrix proved to be a great base for receiving the active purposes. The "in vivo" assays showed a promising application to apply in the cicatrization process, deposited directly in the dissemination of the lesions, and the hydrogels with Calendula officinalis presented a better contribution to the size reduction of the fertilizer.